Coherence Analysis: A Comparison Study of Undergraduate Thesis Abstracts at Muhammadiyah Universities - Feti Yuhariah; Safnil Arsyad (Journal of English for Specific Purposes in Indonesia, 2023)
The purpose of this study is to compare the coherence in abstract section of the thesis at the English Education Study Program in three Muhammadiyah Universities. The method in this study was descriptive qualitative. The corpus of the study was 30 abstracts Section of Undergraduate Student's Thesis which were obtained online through the repository from three different Muhammadiyah universities. In this research, the researcher used theory of analysis from Mayring (2014). The data was taken from (1) Muhammadiyah University of Bengkulu; (2) Muhammadiyah University of North Sumatra; and (3) Muhammadiyah University of Yogyakarta. The results of this study obtained a coherent comparison which is the University of Muhammadiyah Bengkulu had a level of incoherence of 62.7%, the University of Muhammadiyah Yogyakarta had a level of incoherence of 62.5%, and the University of Muhammadiyah Sumatra Utara had incoherence level of 57%. In conclusion, the abstracts thesis by three different English Education Study Programs of Muhammadiyah Universities were still have incoherence with a score between 62% -57%, which means that there must be an increase in order to take into account the level in achieving coherence of an abstract so that it will be easily understood by the reader.